Efeitos do treinamento de força na água após um período de destreinamento em mulheres idosas praticantes de hidroginástica - Rodrigues, Henrique Franca [UNIFESP] (2020)
Interruption of a training program by the elderly can lead to decreased functional capacity and health complications, and retraining with higher intensity exercises can improve this status. Objective: to quantify the changes in muscle strength and functional capacity that occur with a retraining program with Water Strength Training (TFA) after a period of retraining an elderly women practicing Hydrogymnastics (Hydro). Methods: 174 elderly women practicing Hydro (minimum 6 months) (68.6 ± 5.90 years; 71.58 ± 12.54 kg; 29.15 ± 4.68 kg / m²) underwent three evaluations at different times. different: moment1 (M1) immediately before the interruption of the Hydro program, moment 2 (M2) after 12 weeks of detraining, moment 3 (M3) after 12 weeks of retraining with TFA with 45 minutes / day sessions twice a week. Maximum voluntary isometric contraction strength of the lower and upper limbs (Commander Echo MMT System-J Tech Medica dynamometer) and functional capacity were assessed using the Time Up and Go (TUG) agility test and 6-minute walk test (6MWT). Results: Muscle strength decreased with detraining (p≤0.001) and increased in retraining with TFA when compared to detraining (m2) (p≤0.001) and baseline (M1) (p≤0.001). As for functional capacity, there was no significant reduction with detraining and significant improvement with retraining when compared to baseline (M1) (p≤0.001). Conclusion: Retraining with TFA increases muscle strength and functional capacity after a detraining period in elderly women practicing hydrogymnastics.